(untitled) (Journal of Dhaka Medical College, 2016)
Background: Fibromyalgia tender points (FMTP) have consistently reported higher number count in systemic lupus erythematosus (SLE) patients compared with the general population. Objective: The purpose of this study was to determine the association and impact of fibromyalgia tender points on disease activity in SLE patients. Methods: Sixty seven female SLE patients and equal number of asymptomatic, age and sex matched control subjects were enrolled in this observational study. The study was performed between April 2005 and October 2006. After fulfilling the certain inclusion criteria, obtained data were recorded in a structured questionnaire. 18 FMTP sites and 6 control sites were examined by standardized manual tender point survey system. Systemic lupus erythematosus disease activity index (SLEDAI) was used covering all 9 organs and 24 descriptors with pre assigned severity weights. The scores ranged from 0 ( no disease activity) to 105 ( maximum disease activity). Both the SLE cases and the control group were classified into two subgroups namely 0-10 FMTP having 10 or less FMTP and >11 FMTP bearing 11or more tender points. Results: The age (mean ± SD) of the SLE patients and controls were 26.82 ± 8.02 and 29.67± 10.80 years respectively. No significant difference in age (p = 0.091) and in family income (p = 0.065) was observed but significant difference was observed in level of education ( p = 0.009) and in occupation ( p = 0.004) . At enrolment, the number of FMTP (mean ± SD) in SLE patients and control groups were 8.80±6.40 and 3.63±4.90 respectively. The difference was significant (p<0.001). The SLEDAI score (mean ± SD) in SLE patients was 11.75±9.85. Further, the SLEDAI score of 0-10 FMTP and >11FMTP subgroups of SLE were 8.49±7.34 and 17.58±11.17 respectively. The difference was again significant (p<0.001). Hence the disease activity was positively correlated (r=+0.439, p<0.001) with FMTPs in SLE patients. Meanwhile, no significant correlation was observed between disease duration (r= +0.085, p = 0.495) and SLEDAI and similarly no significant correlation was also observed in disease duration with FMTP; 0-10 and >11FMTP groups of SLE (p = 0.605) Conclusions: SLE patients with higher number of FMTPs are significantly associated with increased scores of SLEDAI. Hence, it can be said that there is a linear correlation between the number of FMTPs and the disease activity in SLE patients. Interestingly, no significant correlation was observed between disease duration and SLEDAI as well as between disease duration and FMTP. J Dhaka Medical College, Vol. 24, No.2, October, 2015, Page 99-107